Why dictators veto: legislation, legitimation and control in Kazakhstan and Russia. Issue 2 (17th February 2020) - Köker, Philipp
ABSTRACT: Why do authoritarian presidents still use their legislative power? Although recent studies have argued that authoritarian legislatures are more than "rubberstamps" and can serve as arenas for elite bargaining over policy, there is no evidence that legislators would pass bills that go against presidential preferences. This article investigates this apparent paradox and proposes a theoretical framework to explain presidential activism in authoritarian regimes. It argues that any bills that contravene constraints on policy-making set by the president should generally be stopped or amended by other actors loyal to the regime. Thus, presidents will rather use their veto (1) to protect the regime's output legitimacy and stability, and/or (2) to reinforce their power vis-à-vis other actors. The argument is tested using two case studies of veto use in Kazakhstan and Russia over the last 10 years. The analysis supports the propositions of the theoretical framework and furthermore highlights the potential use of vetoes as a means of distraction, particularly in relation to international audiences. The article extends research on presidential veto power to authoritarian regimes and its findings contribute to the growing literature on the activities of authoritarian legislatures.